SURGICAL TREATMENT OF SERTOLI CELL TUMORS EXTRATESTICULAR BY SCROTAL SAC ABLATION IN A LOCAL DOG - Negara, Made Baruna Yuwana Negara; Wirata, I Wayan; Pemayun, I Gusti Agung Gde Putra (Buletin Veteriner Udayana, 2026)
Sertoli cell tumor is an abnormal tissue growth or neoplasm that most frequently occurs in the genital system of male dogs and can occur outside the testicular organ (extratesticular). This tumor arises from the sex cord-stromal support tissue, which consists of granulosa cells, Sertoli cells, and Leydig cells. This report aims to document the management of a Sertoli cell tumor case in a male local dog through scrotal ablation surgery. A seven-year-old male local dog named Boby, weighing 17 kg, presented with a solid mass on the scrotum that had been present for one year and was progressively increasing in size. Ancillary diagnostic procedures via histopatology of the testis revealed a proliferation of columnar cells with visible mitosis and tumor cells with a tubular pattern between trabeculae, leading to a diagnosis of Sertoli cell tumor with a favorable prognosis. Treatment was performed through scrotal ablation surgery to remove the entire tumor mass attached to the dog's scrotum, followed by an orchiectomy. Postoperatively, long-acting amoxicillin (15 mg/kg BW) was administered subcutaneously (SC) q48h on days 0, 2, 4, 6, and 8, followed by supportive therapy with biodin (2 ml) intramuscularly (IM) on the same schedule. On day 10, the surgical wound had begun to heal and showed no signs of infection; the dog exhibited normal appetite, water intake, urination, and defecation. These results indicate that scrotal ablation is an effective treatment for Sertoli cell tumors in dogs. Postoperatively, it is recommended to keep the dog in a cage and use an Elizabethan collar to prevent secondary infection.